Pengaruh Kinerja Lingkungan, Kinerja Keuangan dan Kepemilikan Manajerial terhadap Nilai Perusahaan Dengan Pengungkapan Corporate Social Responsibility (CSR) sebagai Variabel Moderating - Indah Kristianti; Dewi Susiana Maulida (Sekolah Pascasarjana Perbanas Jakarta, 2023)
The purpose of this study was to analyze the effect of managerial ownership, environmental performance and financial performance on firm value with Corporate Social Responsibility (CSR) as the moderating variable. The independent variables used are managerial ownership, environmental performance and financial performance. The dependent variable used is firm value. The moderating variable used is Corporate Social Responsibility (CSR). The population in this study is a coal mining company registered in the Indonesian Stock Exchange. The sampling method used is the causal method with a sample of 13 companies during the observation period of 4 consecutive years so that the total sample is 52. The method of analysis of this study uses multiple linear regression and moderating regression analysis. The results of this study indicate that managerial ownership has no effect on firm value, environmental performance has no effect on firm value, financial performance has no effect on firm value, Corporate Social Responsibility (CSR) cannot moderate the relationship between managerial ownership and firm value, Corporate Social Responsibility (CSR) ) can moderate the relationship between environmental performance and firm value, Corporate Social Responsibility (CSR) cannot moderate the relationship between financial performance and firm value. Keywords: Managerial Ownership, Environmental Performance and Financial Performance, Company Value, Corporate Social Responsibility (CSR).